EZH2 inhibitors restore epigenetically silenced CD58 expression in B-cell lymphomas. (March 2020) - Otsuka, Yasuyuki; Nishikori, Momoko; Arima, Hiroshi; Izumi, Kiyotaka; Kitawaki, Toshio; Hishizawa, Masakatsu; Takaori-Kondo, Akifumi
Highlights: Loss of CD58 is a common mechanism for immune evasion in lymphoid malignancies. EZH2 inhibitors restore epigenetically suppressed CD58 expression of lymphoma cells. EZH2 inhibitors enhance IFN-γ production of T and NK cells against lymphoma cells. Abstract: Loss of CD58 is a common mechanism for tumor immune evasion in lymphoid malignancies. CD58 loss is known to occur due to both genetic and non-genetic causes; therefore, we hypothesized that restoring CD58 expression in lymphoma cells may be an effective treatment approach. To explore the potential for restoring CD58 expression, we first screened 11 B-cell lymphoma lines and found that 3 had decreased CD58 expression. Among these, CD58 was genetically damaged in two lines but not in the third line. Using the cell line with downregulated CD58 without a genetic abnormality, we performed epigenetic library screening and found that two EZH2 inhibitors, EPZ6438 and GSK126, specifically enhanced CD58 expression. By examining the effect of three EZH2 inhibitors with different selectivity profiles in different B-cell lines, EZH2 inhibition was shown to have a common activity in upregulating CD58 expression. Restoring the expression of CD58 in lymphoma cells using an EZH2 inhibitor was shown to enhance interferon-γ production of T and NK cells against lymphoma cells. H3K27 was shown to be highly trimethylated in the CD58 promoter region, and EZH2 inhibition induced its demethylation and activated transcription of the CD58 gene. These results indicated that EZH2 is involved in the epigenetic silencing of CD58 in lymphoma cells as a mechanism for tumor immune escape, and EZH2 inhibitors are able to restore epigenetically suppressed CD58 expression. Our findings provide a molecular basis for the combination of an EZH2 inhibitor and immunotherapy for lymphoma treatment.